Complete Genome Sequence of Pseudomonas balearica Strain EC28, an Iron-Oxidizing Bacterium Isolated from Corroded Steel - Salgar-Chaparro, Silvia J. (Microbiol Resour Announc, 2020)
Pseudomonas balearica strain EC28 is an iron-oxidizing bacterium isolated from corroded steel at a floating production storage and offloading facility in Australia. Here, we report its complete genome sequence, which comprises 4,642,566 bp with a GC content of 64.43%. The genome harbors 4,164 predicted protein-encoding genes.